2020
DOI: 10.3390/ijerph17061857
|View full text |Cite
|
Sign up to set email alerts
|

Home Assessment of Indoor Microbiome (HAIM) in Relation to Lower Respiratory Tract Infections among Under-Five Children in Ibadan, Nigeria: The Study Protocol

Abstract: The association between household air pollution and lower respiratory tract infections (LRTI) among children under five years of age has been well documented; however, the extent to which the microbiome within the indoor environment contributes to this association is uncertain. The home assessment of indoor microbiome (HAIM) study seeks to assess the abundance of indoor microbiota (IM) in the homes of under-five children (U-5Cs) with and without LRTI. HAIM is a hospital- and community-based study involving 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…We found only one study 22 that reported IM assessment using dust sampling technique in addition to air sampling method. Similar studies 44‐47 suggested that settle dust sampling methods such as the electrostatic dustfall collector (EDC) reflect the microbial composition of indoor air. They further emphasized that EDC tends to predict better microbial levels in indoor air and is more reproducible.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found only one study 22 that reported IM assessment using dust sampling technique in addition to air sampling method. Similar studies 44‐47 suggested that settle dust sampling methods such as the electrostatic dustfall collector (EDC) reflect the microbial composition of indoor air. They further emphasized that EDC tends to predict better microbial levels in indoor air and is more reproducible.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, some innovative techniques have been developed to investigate airborne viruses in the indoor environment. These techniques include the SKC AirCheck pumps loaded with filter holders, Sioutas Personal Cascade Impactor Sampler (PCIS), and recently the EDCs coupled with laboratory analysis using the quantitative polymerase chain reaction (qPCR) assay 47,58‐60 . These methods can be applied to comprehensively study the association between exposure to IM including aerosolized viral agents and LRTI risk among U‐5C.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and sites are detailed elsewhere. 15 , 19 Briefly, 178 cases were matched to 180 controls for sex, age (±3 months), and geographical location. Severe LRTI cases were recruited from three hospitals within Ibadan, namely Otunba-Tunwase Children Emergency Clinic of the University College Hospital, Ade-Oyo Maternity Teaching Hospital, and Oni-memorial Children Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the study protocol, and recruitment procedures have been published elsewhere. [22] At the presenting hospital, children were screened and those who met the eligibility criteria (< 5 years of age; admitted for LRTI; and residing in Ibadan), and whose caregivers gave consent, were included in the study. Diagnosis of LRTI in children was carried out by a paediatrician based on chest radiography including the presence of one or more of the chest radiographic features of patchy, segmental, or lobar consolidation; +/-a positive air bronchogram; and +/-pleural effusion.…”
Section: De Nition and Selection Of Cases And Controlsmentioning
confidence: 99%